Role of G Protein-Coupled Receptors in Hepatic Stellate Cells and Approaches to Anti-Fibrotic Treatment of Non-Alcoholic Fatty Liver Disease - Kimura, Takefumi; Singh, Simran; Tanaka, Naoki; Umemura, Takeji (Frontiers in Endocrinology, 2021)
The prevalence of non-alcoholic fatty liver disease (NAFLD) is globally increasing. Gaining control over disease-related events in non-alcoholic steatohepatitis (NASH), an advanced form of NAFLD, is currently an unmet medical need. Hepatic fibrosis is a critical prognostic factor in NAFLD/NASH. Therefore, a better understanding of the pathophysiology of hepatic fibrosis and the development of related therapies are of great importance. G protein-coupled receptors (GPCRs) are cell surface receptors that mediate the function of a great variety of extracellular ligands. GPCRs represent major drug targets, as indicated by the fact that about 40% of all drugs currently used in clinical practice mediate their therapeutic effects by acting on GPCRs. Like many other organs, various GPCRs play a role in regulating liver function. It is predicted that more than 50 GPCRs are expressed in the liver. However, our knowledge of how GPCRs regulate liver metabolism and fibrosis in the different cell types of the liver is very limited. In particular, a better understanding of the role of GPCRs in hepatic stellate cells (HSCs), the primary cells that regulate liver fibrosis, may lead to the development of drugs that can improve hepatic fibrosis in NAFLD/NASH. In this review, we describe the functions of multiple GPCRs expressed in HSCs, their roles in liver fibrogenesis, and finally speculate on the development of novel treatments for NAFLD/NASH.